Clinical analysis of prolonged viral clearance time in patients with lymphoma combined with novel coronavirus infection - Li, Ying; Wu, Chao; Fei, Liming; Xu, Qin; Shao, Xianru; Chen, Bangjie; Sun, Gengyun (Frontiers in Molecular Biosciences, 2023)
To compare the period of viral clearance and its influencing factors after severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection between patients with lymphoma and lung cancer. Methods We retrospectively collected the clinical data of patients with lymphoma and lung cancer (118 cases) diagnosed with SARS-CoV-2 infection and hospitalized in the First Affiliated Hospital of Anhui Medical University between December 1, 2022, and March 15 2023. Finally, 87 patients with prolonged virus clearance times were included and divided into lymphoma (40 cases) and lung cancer (47 cases) groups. We used the Kaplan–Meier method to draw a negative turn curve. We performed a univariate analysis of the prolongation of virus clearance time and a Cox regression model for multivariate analysis. Results The median times for viral clearance in the lung cancer and lymphoma groups were 18 (95% confidence interval [CI] 15.112–20.888) and 32 (95%CI 27.429–36.571) days, respectively. Log-rank analysis showed a statistically significant difference (P=0.048), and the lymphocyte count in the lymphoma group was lower than that in the lung cancer group (P=0.044). We used the Cox regression model to conduct a multivariate analysis, which revealed that in lymphoma patients, the interval between the time of diagnosis and the time of SARS-CoV-2 infection <24 months (hazard ratio [HR]: 0.182, 95%CI: 0.062–0.535, P=0.02), an interval between the last anti-CD20 monoclonal antibody treatment and the time of SARS-CoV-2 infection of <2 months (HR: 0.101, 95%CI: 0.029–0.358, P<0.001), and a decrease in peripheral blood lymphocyte levels (HR: 0.380, 95%CI: 0.179–0.808, P=0.012) were independent risk factors for prolonged viral clearance time. Conclusion Patients with lymphoma combined with SARS-CoV-2 infection had a longer virus clearance time than did patients with lung cancer. Moreover, the lymphocyte count in the lymphoma group was lower than that in the lung cancer group; therefore, the immune status of patients with lymphoma is lower than that of patients with lung cancer. An interval between lymphoma diagnosis and SARS-CoV-2 infection of <2 years, anti-CD20 monoclonal antibody treatment within the past 2 months, and a decrease in lymphocyte levels in the peripheral blood prolonged the virus clearance time in the patients in this study.